The development and evaluation of a mu-capture ELISA detecting Chlamydia-specific IgM. - Wreghitt, T. G. (Cambridge University Press, 1988)
A mu-capture enzyme-linked immunosorbent assay (ELISA) for detecting chlamydia-specific IgM was developed by use of the heat stable, lipopolysaccharide group-specific antigen and an alkaline phosphatase-labelled anti-chlamydia group-specific monoclonal antibody conjugate. The test was used to study the serological response in chlamydial respiratory tract infection among patients with acute respiratory tract symptoms in Cambridgeshire during the past 7 years. Results were compared with those of the complement fixation test (CFT) in routine use as well as those of a whole inclusion indirect immunofluorescence (WIF) test for IgM. Correlation between results of the mu-capture ELISA and those of the WIF test was 87.5%. The percentage of patients in whom specific IgM was found fell with increasing age. This may be due to lack of recall of IgM as a response to reinfection. Chlamydia-specific IgM was more likely to be detected when the CFT titre was greater than or equal to 64 and was rarely detected more than 6 months after the onset of symptoms. However, several patients less than 20 years of age were found to have specific IgM with CF antibody titres less than 64. We have found the mu-capture ELISA a useful test for the diagnosis of respiratory tract chlamydial infections, particularly in younger patients.